Cognitive reserve may outperform age, mood and psychiatric comorbidities as a predictor of executive functioning in bipolar disorder and healthy adults. Issue 6 (3rd July 2021) - Cotrena, Charles; Branco, Laura Damiani; Ponsoni, André; Shansis, Flávio Milman; Fonseca, Rochele Paz
ABSTRACT: Introduction: Cognitive reserve plays a protective role against executive dysfunction in healthy adults and individuals with psychiatric illnesses such as bipolar disorder. However, the magnitude of the influence of cognitive reserve on specific executive functions (EFs), and its impact relative to variables such as depressive symptoms, age and psychiatric comorbidities, is unexplored. This study aimed to quantify the influence of cognitive reserve on specific EFs, and compare its impact with that of depressive symptoms, age and psychiatric comorbidities, in separate models for patients with bipolar disorder and healthy adults. Method: This was a cross-sectional study of 121 adults with no mood disorders and 109 with bipolar disorder, all of whom underwent a comprehensive psychiatric assessment and evaluation of the EFs. Cognitive reserve was measured using years of education, IQ and reading and writing habits. The association between EFs and predictors (cognitive reserve, depressive symptoms, age and psychiatric comorbidities) was evaluated through structural equation modeling. Four models were constructed for each group independently (bipolar disorder and control), one each for working memory, verbal fluency, inhibition and flexibility, due to group differences in age and cognitive reserve. Results: Working memory, inhibition and flexibility were most significantly predicted by cognitive reserve and age. Verbal fluency was only predicted by cognitive reserve. Comorbidities and depressive symptoms were not significant in any of the models. Cognitive reserve had a positive influence on all EFs in models for patients with bipolar disorder and models for control participants. Age had a negative impact on three of the four EFs tested. Conclusion: Fostering cognitive reserve through continued education and cognitively stimulating leisure activities may be an effective intervention for executive dysfunction in patients and non-patients alike. In some cases, the effects of these interventions may outweigh the negative cognitive impact of aging, depressive symptoms and psychiatric conditions.